On One Case of Existence of Homogeneous Solutions - Dorogovtsev, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We present necessary and sufficient conditions for the existence of a homogeneous solution for a class of partial differential equations with a homogeneous random perturbation in a Banach space.